Exceso de peso corporal en estudiantes universitarios según variables sociodemográficas y estilos de vida (2017)
ABSTRACT: Introduction: University students are particularly vulnerable to inadequate food intake, which has consequences for their nutritional and health status. Objective: To study the prevalence of overweight (OW) and its associated factors among a group of students at University of Antioquia, Colombia. Materials and Methods: Cross-sectional study involving 424 male and female students 21.4±4.0 years of age. OW was diagnosed by body mass index (BMI) ≥ 25 kg/m2; risk of central adiposity was measured by waist circumference (WC) ≥ 90 cm and ≥ 80 cm in men and women, respectively. Socio-demographic and lifestyle variables were measured. Chi2 test (α= 0.05) was used as a descriptive statistic. Results: 17.1% of students had OW, which was higher in men (men: 22.6% vs women 14.0%, p< 0.05); 8.1% had risk of central adiposity higher, which was higher in women (men: 6.5% vs women: 9.1%, p> 0.05). BMI was associated with sex (p= 0.001). Risk of central adiposity was not related with socio-demographic or lifestyle characteristics. Conclusion: A considerable percentage of university students were overweight based on BMI, which related to sex of the student. However, it is important to promote university spaces that are conducive to healthy lifestyles.